Entomological Survey and Temephos Susceptibility of Aedes, Culex and Anopheles in Naena Muktipura Mimika Papua - Novyan Lusiyana (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Arthropod-borne diseases are infectious diseases mediated by mosquitoes that have incurred a considerable health problem. The prevalence of this disease is notably high in some rural areas, such as Papua, due to some environmental conditions that support mosquitoes breeding sites and leads to high rate of disease transmission. Methods: This experimental research aims to determine the breeding site, mosquitos' diversity, and susceptibility to temephos insecticide through an entomological survey to find out the breeding site of the larvae. The positive breeding sites of the larva were captured and identified in the laboratory. The temephos test were carried out for each species of larvae at dose 0,02 ppm for Aedes albopictus and Culex sp, and 0.25 ppm for Anopheles sp. Results and Discussion: Entomology survey showed that 5 of 27 stagnant water were positive breeding site of mosquito larvae. The following larvae were found: Aedes sp, Culex sp and Anopheles sp. Culex sp and Anopheles sp prefer dirty stagnant water covered with leaves, while Aedes albopictus likes puddles that are exposed to direct sunlight. The three species were known to be susceptible to temephos. Conclusion: There are three species of Diptera in Naena Muktipura village, with different characteristics of breeding site, but those mosquitoes are all susceptible to temephos.